Subgrade stabilization by using fly ash, case study in Universiti Malaysia Pahang (UMP) - Nur Atiqah, Hussin (2010)
This project is to evaluate the different percentages of fly ashes and different water content for the stabilization of silt soil of sub graded from UMP location in Pahang. Initially, the soil-fly ash mixtures have been analyzed. It has also been researched if it is possible to use as soil stabilization or not. For the research, few experiment have been carried out by using experiment sample such as moisture content, particle size analysis, atterberg limit, compaction test, CBR and specific gravity. As the result of the experiment research, it has been observed and determined that soil- fly ash mixture with different percentages fly ash and water content can be used as soil stabilization of highway and the stabilization material when building highway and every land of road and it also been observed and determined that the increased strength of the mixed material.